Answers

The Brainliest Answer!
  • Brainly User
2015-09-02T22:45:25+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let x be the second number.

Representation:
      First number = 2x  (twice the second number)
      Second number = x
      Third number = (2x+x) + 4 (four more than the sum of the first two numbers)
      Fourth number = (2x-x) - 3  (three less than the difference of first two numbers)
      Total of the four numbers = 92

Equation:
    2x + x + (2x+x+4) + (2x-x-3) = 92
   2x + x + 3x + 4 + x-3 = 92

Combine the like terms:
   2x + x + 3x + x + 4 - 3 = 92
   7x +1 = 92
   7x = 92-1
   7x = 91
   7        7
   x = 13 

The numbers are:
  first number = 2x  
                        = 2(13)
                        = 26

   second number = x
                                = 13

   third number =  2x + x + 4
                           = 2 (13) + 13 + 4
                           = 26 + 13 + 4
                           = 43
 
   fourth number =  2x-x-3
                             = 2(13) - 13 - 3
                             = 26 - 13- 3
                              = 10

To check:
     26 + 13 + 43 + 10 = 92
                                 92 = 92    



   

1 5 1